Thermal performance optimization of a semi-nested building coupled with an earth-to-air heat exchanger using iterative Taguchi method. (August 2022) - Lin, Yaolin; Feng, Haoming; Yang, Wei; Hao, Xiaoli; Tian, Lin; Yuan, Xingping
Abstract: In this paper, a semi-nested building coupled with an earth-to-air heat exchanger is investigated to maintain indoor thermal comfort and reduce building energy consumption. Firstly, the computer models on the semi-nested building coupled with earth-to-air heat exchanger were developed under the TRNSYS environment. Secondly, the simulation results from the computer models were validated with experimental data from open literature. Finally, iterative Targuchi method was employed to find the optimal design values for the envelope properties and earth-to-air heat exchanger configurations. The optimal values of the design parameters were found to be A1 (window-to-wall ratio of 10%), B3 (triple-layer Low-E glazing window), C3(insulation thickness of 200 mm for external wall), D3 (concrete slab thickness of 250 mm for external wall), E3(absorption of solar radiation for external walls of 0.75), F3(absorption of solar radiation for the roof of 0.75), G5 (earth tube inner diameter and air gap of 300 mm and 400 mm, respectively), H2 (earth tube length of 50 m), and I3 (duct air velocity of 1.5 m/s).